ÍNDICE DENTARIO DE TÜBINGEN MODIFICADO APLICADO EN NIÑOS MESTIZOS PERUANOS COMPRENDIDOS ENTRE 4 Y 6 AÑOS DE EDAD, EN EL DISTRITO DE SURQUILLO - Neira Mendoza, Oscar Calixto (2000)
In this study, 50 male children between 4 and 6 years of age were examined, they were selected from a group of children with normooclusion, models were measured according to objetive of the research work of Dr. Dausch-Neumann of the University of Tübingen Germany in 1976; Ressults were procesed trough a computarized statstic program and the numeric values obtained were used for the measures of the incisal area in deciduos dentition of the peruvian children to early diagnostic of diferents maloclusions.